2007
DOI: 10.1177/1363461507074976
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Psychosis in Uganda

Abstract: A qualitative study, investigating the representations and explanatory models of ;madness' held by indigenous and religious healers, was undertaken in urban Uganda. Case vignettes of individuals with a diagnosis of a psychotic disorder were discussed by the healers in terms of phenomenology, causality, intervention and outcome. Indigenous healers primarily understood ;madness' as spiritual or physiological, whereas religious healers also held psychological models. Healers' understandings of ;madness' are inext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…Some examples include (a) communities that are more able to tolerate and protect consumers (e.g., within the Jamaican population) (34); (b) social solidarity by offering work opportunities in local businesses (e.g., tribal or village associations in Latin America) (35); (c) participation in traditional and religious healing rituals such as musical rituals in Sudanese culture (36); (d) more flexible job requirements (e.g., agrarian work within rural China) (37); (e) family and extended kinship or a communal network to support individuals with a mental disorder (e.g., kinship ties in Ethiopia and Tanzania) (38); and (f) attribution of cultural or spiritual value to psychotic experiences such as visions, or what might be interpreted as prophetic encounters (e.g., Uganda) (39). We propose that to most effectively implement anti-stigma interventions in LMICs, interventions might best leverage these existing strengths to combat the severe mental illness stigma and discrimination that occurs within these contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples include (a) communities that are more able to tolerate and protect consumers (e.g., within the Jamaican population) (34); (b) social solidarity by offering work opportunities in local businesses (e.g., tribal or village associations in Latin America) (35); (c) participation in traditional and religious healing rituals such as musical rituals in Sudanese culture (36); (d) more flexible job requirements (e.g., agrarian work within rural China) (37); (e) family and extended kinship or a communal network to support individuals with a mental disorder (e.g., kinship ties in Ethiopia and Tanzania) (38); and (f) attribution of cultural or spiritual value to psychotic experiences such as visions, or what might be interpreted as prophetic encounters (e.g., Uganda) (39). We propose that to most effectively implement anti-stigma interventions in LMICs, interventions might best leverage these existing strengths to combat the severe mental illness stigma and discrimination that occurs within these contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Lay descriptions of psychotic disorders in Sub-Saharan Africa emphasize behavioural disturbance and disruption of social norms, yet do not often contain symptoms related to thought disturbance and perceptual symptoms [23-25]. The list of characteristics of people with ‘psychosis’, reported by respondents from four East African ethnic groups in a classical study by Edgerton [26], included: walking naked, being violent, arson, and talking nonsense.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that people living in western countries focus mainly on biological and social risk factors such as genetic vulnerability, disease of the brain, infection or stressful social conditions or personal weakness [1-4], but the predominant views held by people living in non-western countries focus mainly on supernatural and religious factors [5-9]. In a cross-cultural study comparing Australia and Japan, infection, allergies and genetics were the most commonly attributed causes of mental illness reported in Australia; whereas, nervousness and perceived constitutional weakness were more often reported in Japan [3].…”
Section: Introductionmentioning
confidence: 99%